Palm Oil Fuel Ash and Fly Ash for a Partial Replacement of Cement in High-Quality, Environmentally Friendly Mortar as a Solution to Industrial Waste - Siregar, Shinta Marito; Humaidi, Syahrul; Bukit, Nurdin; Frida, Erna (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study explores the effects of incorporating palm oil fuel ash (POFA) and fly ash (FA) as partial cement substitutes on the mechanical properties and characteristics of high-quality mortar, specifically Engineered Cementitious Composites (ECC). ECC mortar was fabricated by milling POFA waste and FA through a top-down method utilizing a ball mill. The resulting material was subjected to tests for slump flow, water absorption, compressive strength, and characterized through XRF, FTIR, SEM/EDX, and XRD analyses. FTIR analysis verified the existence of Si-O and Al-O groups within the composite made of POFA-FA ECC. XRF analysis of FA and POFA showed cementitious properties, with SiO2+Al2O3+Fe2O3 exceeding 50% and CaO surpassing 10%. SEM and XRD results indicated minimal cavity formation, suggesting a high compressive strength in the mortar. Particle size distribution analysis revealed prevalent particles in the 1.5×10−1 to 2.0×10−1 μm range. The compressive strength test after 28 days, incorporating 15% FA and 10% POFA, yielded the highest strength at 59.30 MPa. The water absorption values ranged from 1.25% to 2.67%, indicating that POFA-FA assists in the cement hydration process and also serves as a filler. As a result, the material’s density is very high, leading to fewer voids formed, thus reducing the trapped water, which significantly affects the mortar’s strength.